Correlation between the Reduced Circulating Endothelial Progenitor Cell Counts and Elevated Intraocular Pressure-Induced Retinal Ganglion Cell Apoptosis. (11th July 2014) - Yao, Baoqun; Zhao, Qing; Yan, Hua; Chen, Fanglian; Liu, Li
ABSTRACT: Purpose : To investigate the correlations between intraocular pressure (IOP) and circulating endothelial progenitor cells (EPCs), retinal ganglion cells (RGC) apoptosis and EPCs, and explore the possible role of EPCs in the elevated IOP-induced RGC apoptosis. Materials and methods : A rat model of IOP elevation was induced by photocoagulation of the limbus vein and episcleral veins using a 532-nm green laser. Twenty rats were randomly assigned to normal control (NC) group, 30 rats were randomly assigned to sham-treated control (STC) group and 50 rats were randomly assigned to laser-treated (LT) group. The IOPs were measured with a Tono-pen XL tonometer. Hematoxylin-eosin staining was performed to observe the effects of IOP elevation on the structure of retina. Retinal apoptotic cells were determined by in situ TUNEL staining, and peripheral blood EPCs (CD34 + /CD133 + ) were detected by flow cytometry. Results : Compared with the NC group (9.9 ± 1.2 mmHg), the IOPs in the LT group were 37.4 ± 1.5, 31.8 ± 4.1, 25.9 ± 2.2, 23.1 ± 3.6 and 22.4 ± 3.0 mmHg on the third day, seventh day, third week, second month and third month, respectively, after the laser photocoagulation. There were significant differences in IOPs between the groups at the different time points ( F  = 110.02, p  < 0.001). TUNEL analysis showed that only few apoptotic RGCs were found on the third and the seventh day after the laser treatment, and then many more apoptotic RGCs were found beginning on the third week after the laser treatment. The EPC counts were 121.3 ± 22.4, 81.3 ± 23.7, 46.1 ± 15.8, 54.4 ± 19.1 and 54.7 ± 15.9 /2 × 10 5 mononuclear cells (MNCs) on the third day, seventh day, third week, second month and third month, respectively, after the laser photocoagulation, compared with the NC group (62.1 ± 13.1)/2 × 10 5 MNCs. There were significant differences in EPC counts between the groups at the different time points ( F  = 22.09, p  < 0.001). Conclusions : Elevated IOP-induced RGC apoptosis is associated with the reduced circulating EPC counts.